Предмет: Алгебра,
автор: timosis
Решите уравнение
(х+6)(х-1)-(х+3)(х-4)=5х
30б
Ответы
Автор ответа:
0
(x+6)(x-1)-(x+3)(x-4)=5x
x2+6x-x-6-(x2+3x-4x-12)=5x
x2+6x-x-6-x2-3x+4x+12=5x
6x+6=5x
6x-5x= -6
x= -6
x2+6x-x-6-(x2+3x-4x-12)=5x
x2+6x-x-6-x2-3x+4x+12=5x
6x+6=5x
6x-5x= -6
x= -6
Автор ответа:
0
Если не сложно пож: 14х^2-(2х-3)(7х+4)=14
Автор ответа:
0
^ - это умножить?
Автор ответа:
0
тож уравнение пож!!!
Автор ответа:
0
^ нет это степень^^^^
Похожие вопросы
Предмет: Математика,
автор: 20011981b
Предмет: Английский язык,
автор: istkirillka
Предмет: Биология,
автор: BelliPokers
Предмет: Математика,
автор: PSnatasha321